2020
DOI: 10.1002/nau.24310
|View full text |Cite
|
Sign up to set email alerts
|

Urethral dysfunction and therapeutic effects of a PDE 5 inhibitor (tadalafil) in a rat model of detrusor underactivity induced by pelvic nerve crush injury

Abstract: Aims The urethral dysfunction produced by a rat model of peripheral neurogenic detrusor underactivity (DU) using pelvic nerve crush (PNC) injury was characterized and then tested with the administration of tadalafil, a phosphodiesterase type 5 (PDE 5) inhibitor. Methods Ten days after producing PNC rats, awake cystometrograms (CMGs) and isovolumetric cystometrograms with urethral perfusion pressure (IC‐UPP) measurements were performed. Also, in control rats, IC‐UPP was recorded before and after intravenous atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(58 reference statements)
0
2
0
2
Order By: Relevance
“…Recently, Matsukawa et al conducted a study that found that both tadalafil and silodosin had a significant impact on improving LUTS and voiding function in patients with non-neurogenic DU, and that tadalafil was associated with an improvement in BCI (19.7 ± 17.7 vs. 6.0 ± 12.5, p < 0.001) and Q max (3.0 ± 3.0 mL/s vs. 1.7 ± 1.4, p < 0.001) [116]. The mechanism of action of tadalafil may be linked to enhanced urethral relaxation [117], increased blood flow to the lower urinary tract [118], improved oxygenation [119], and decreased chronic inflammation [120] of the bladder and prostate.…”
Section: Phosphodiesterase 5 Inhibitors (Pde5is)mentioning
confidence: 95%
“…Recently, Matsukawa et al conducted a study that found that both tadalafil and silodosin had a significant impact on improving LUTS and voiding function in patients with non-neurogenic DU, and that tadalafil was associated with an improvement in BCI (19.7 ± 17.7 vs. 6.0 ± 12.5, p < 0.001) and Q max (3.0 ± 3.0 mL/s vs. 1.7 ± 1.4, p < 0.001) [116]. The mechanism of action of tadalafil may be linked to enhanced urethral relaxation [117], increased blood flow to the lower urinary tract [118], improved oxygenation [119], and decreased chronic inflammation [120] of the bladder and prostate.…”
Section: Phosphodiesterase 5 Inhibitors (Pde5is)mentioning
confidence: 95%
“…We hypothesize that a considerable number of patients suffering from lower urinary tract symptoms with various possible pathophysiologies including aging 30 have such a condition but are left underdiagnosed because of a lack of clear urodynamically confirmed DU or BOO. 31 We pharmacologically reproduced this condition by administering a combination of atropine and midodrine at doses lower than those used in previous studies, 19,32,33 and applying the experimental methods we used previously 19,20 (Figure 3). In this model, we used the effects of distigmine at 0.003 mg/kg iv as a benchmark because it significantly enhanced the PNS-induced elevation of IVP (Figure 2C) at the plasma concentration similar to that of the clinically efficacious dose (15 mg/man/d) 34,35 (data not shown).…”
Section: Number Of Stoolsmentioning
confidence: 99%
“…Поскольку расслабление гладких миоцитов подпузырной области опосредуется оксидом азота, применение иФДЭ-5 у таких больных также может иметь терапевтический эффект. В недавно опубликованной работе данная концепция была подтверждена в эксперименте [60]. На модели нейрогенной гипоактивности детрузора в сочетании с детрузорно-сфинктерной диссинергией было показано, что назначение тадалафила приводило к достоверному уменьшению объема остаточной мочи и увеличению эффективности мочеиспускания, при этом сократительная активность детрузора не увеличивалась.…”
unclassified
“…На модели нейрогенной гипоактивности детрузора в сочетании с детрузорно-сфинктерной диссинергией было показано, что назначение тадалафила приводило к достоверному уменьшению объема остаточной мочи и увеличению эффективности мочеиспускания, при этом сократительная активность детрузора не увеличивалась. Таким образом, эффективность лечения была достигнута за счет усиления релаксации уретры во время опорожнения, что приводило к повышению эффективности опорожнения [60].…”
unclassified